PELATIHAN PENGELOLAAN CAGAR BUDAYA SEBAGAI OBJEK WISATA PADA MASYARAKAT DI DESA WISATA MATTA BULLU, KABUPATEN SOPPENG - Ugu Saraka, Erwin Mansyur; Rosmawati, Rosmawati; Duli, Akin; Supriadi; Hasyim, Muhammad; Agus, Agus; Sumantri, Iwan (JURNAL KHAZANAH PENGABDIAN, 2023)
Wiasata Matta Bullu Village in Soppeng Regency is a tourism village that is managed independently by the local community in collaboration with BUMDES to form a tourist awareness group (POKDARWIS). The tourist attraction found in the village is the location of the village above an altitude area with beautiful natural scenery, a cool climate, mountainous topography, hills and valleys where the forest is still beautiful, people's livelihoods are generally gardening with grain crops and vegetables, and villages in general with traditional Bugis houses. The type of business in the tourism sector that the community has started is in the form of a waterfall tourist attraction as a recreational location, a creative coffee business named Kopi Matta Bullu, the Petta Bulu Matanre Cemetery as a place of pilgrimage, and homestays (community houses that are rented out to tourists). The dedication of the Department of Archeology at FIB Unhas in 2023 helps the local community manage the cultural heritage (Petta Bulu Mintasre grave) as a tourist attraction with a preservation and sustainable perspective. The result of this assistance is that the local community understands how to preserve cultural heritage and the legal aspects related to it. The Petta Bulu Matanre Tomb Complex is always crowded with pilgrims, especially on religious holidays and other holidays, so that pilgrims (tourists) can be given an understanding and properly managed so as not to damage the cultural heritage as a tourist attraction.